2021
DOI: 10.1111/tid.13665
|View full text |Cite
|
Sign up to set email alerts
|

Microsporidiosis after liver transplantation: A French nationwide retrospective study

Abstract: Background: Microsporidiosis has been largely reported in patients with acquired immunodeficiency syndrome, but emerged as a cause of persistent diarrhea in solid organ transplant patients.Methods: Through the French Microsporidiosis Network and the Groupe français de recherche en greffe de foie, we collected all microsporidiosis cases identified in liver transplant patients between 1995 and 2020 in France.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…It was the first cultivated species, and its genome has been sequenced and annotated ( Katinka et al, 2001 ). It is one of the 17 microsporidian species infecting humans ( González-Machorro et al, 2019 ; Ruan et al, 2021 ), and the third most common species found in humans, with the ability to disseminate to several organs causing a wide spectrum of pathogenesis including encephalitis, nephritis, hepatitis or keratoconjunctivitis ( Ghosh and Weiss, 2012 ; Dumortier et al, 2021 ). All Mo hacking observations described in vitro used this species ( González-Machorro et al, 2019 ; Dalboni et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was the first cultivated species, and its genome has been sequenced and annotated ( Katinka et al, 2001 ). It is one of the 17 microsporidian species infecting humans ( González-Machorro et al, 2019 ; Ruan et al, 2021 ), and the third most common species found in humans, with the ability to disseminate to several organs causing a wide spectrum of pathogenesis including encephalitis, nephritis, hepatitis or keratoconjunctivitis ( Ghosh and Weiss, 2012 ; Dumortier et al, 2021 ). All Mo hacking observations described in vitro used this species ( González-Machorro et al, 2019 ; Dalboni et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of microsporidia in humans came into focus with the emergence of the acquired immune deficiency syndrome (AIDS). In humans severe infection has been seen in patients with AIDS, patients following organ transplantation, and in patients taking immune suppressive drugs or immune modulatory antibodies ( Han and Weiss, 2017 ; Dumond et al, 2021 ; Dumortier et al, 2021 ). Most commonly infection results in a diarrheal syndrome; however, patients may also suffer from encephalitis, ocular infection, sinusitis, myositis, or disseminated infection ( Weber et al, 1994 ; Weiss and Keohane, 2010 ; Ziad et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal microsporidiosis cases are associated with severe and chronic diarrhea in immunocompromized patients [13]. They were first reported as opportunistic infections in HIVinfected patients in the 1980s and 1990s, but nowadays they are mostly diagnosed in other immunocompromized populations, such as patients with solid organ transplantation [3,5,6,8,11,15]. Enterocytozoon bieneusi accounts for more than 90% of intestinal microsporidiosis cases; the remaining cases involve Encephalitozoon intestinalis, Encephalitozoon hellem and Encephalitozoon cuniculi [13].…”
Section: Introductionmentioning
confidence: 99%